Kadar Protein dan Lemak Bakso Daging Ayam Petelur Afkir Dengan Penambahan Ekstrak Buah Patikala (Etlingera Elatior) - Irmawaty, Irmawaty; Herman, Nadia; Mappanganro, Rasyidah (Anoa: Journal of Animal Husbandry, 2024)
Patikala (Etlingera elatior) is a local spice has a fairly high nutritional value, so it has the potential to contribute to improving nutritional values such as protein and fat in processed meal pro duccts such as meatballs. This study aims to determine the protein and fat content of meatballs from culled laying hens with the addition of patikala fruit extract. This research method used a Completely Randomized Design (CRD) cocsisting of 5 treatments and 4 replications. Namely P0 (200 g chicken meat without patikala fruit ekstract), P1 (chicken meat 200 g + 25% Patikala fruit extract), P2 (chicken meat 200 g + 50 % Patikala fruit extract), P3 (chicken meat 200 g + 75% Patikala fruit extract), P4 (chicken meat 200 g + 100% Patikala fruit extract), The data Analiysis used was Analiysis of varians (ANOVA) with Least Significant Doffrent Test (BNT). The parameters used in this study were protein content and fat content. The results of this study indicate that the utilization of Patikala fruit extract to meatballs from culledl laying hens did not have a significant effect (P>0,05) on the protein and fat content of meatballs from culedl laying hens